Habilidades Sociales y acoso escolar: un estudio en centros de Enseñanza Secundaria de Madrid - Dueñas Buey, Mª Luisa; Senra Varela, María (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN Este artículo es el resultado de un estudio de tipo descriptivo con una muestra de adolescentes de eda‐ des comprendidas entre los 13 y 14 años con la finalidad de analizar el fenómeno del acoso escolar, así como la incidencia de ciertas habilidades sociales relevantes en relación con el mismo. Se analiza el acoso escolar a tres niveles diferenciados: bajo, medio y alto en las 9 escalas que componen el instrumento utilizado. También se analizan: • Los niveles de acoso escolar según el sexo. • Las habilidades sociales en función del sexo y, finalmente, • El acoso escolar en función de las habilidades sociales. ABSTRACT The bullying phenomenon is a critically important subject in educational settings as well as in society. The studies conducted in this line show that people with tendency to aggressive behaviour are charac‐ terized by a distinguishable profile: instability, irritability, external attribution, high levels of anxiety, low self‐esteem and tendency to depression. This paper arises from a descriptive study with a sample of adolescents (age from 13 to 14). It is focused on the analysis of the bullying phenomenon and the impact of specific social skills on it. Nine scales of bullying are analysed: harassment, intimidation, threats, coercions, social boycott, social exclusion, social manipulation and aggressions. Likewise, we calculated a global index of bullying, taking three different levels into account: low, medium and high. Social skills measured by the instrument are subsumed by six dimensions: self‐expression in social interactions, defence of the own rights as a consumer, expression of annoyance or disagreement, saying “no” and interrupting social interactions, asking a favour, initiating opposite-sex peer interactions.Furthermore, we performed analysis concerning the following aspects: Levels of bullying by sex. Social skills by sex, and, finally, bullying according to social skills.